Análisis comparativo de los métodos computacionales de análisis aplicados a un sistema de placa de cimentación (2015)
"The system of foundation slabs also known as continuous foundation plates are those foundations that are responsible for transmitting the loads to the ground through a continuous slab that covers the total area of the land occupied by the structure. foundation by means of insulated footings exceeds fifty percent of the construction floor, a foundation is contemplated per plate. "- Excerpt from the text